The general propagator for S-wave threshold states - Hongge Xu; Ning Yu; Zuman Zhang; Guoying Chen (Journal of High Energy Physics)
Abstract We demonstrate that the propagator, derived from an Effective Field Theory (EFT) that incorporates Weinberg’s compositeness theorem, provides a more general formula for describing S-wave near-threshold states. By fitting the lineshape using this propagator, we can extract the Z factor for these states and elucidate their structures.